Modulatory Effects of Motor State During Paired Associative Stimulation on Motor Cortex Excitability and Motor Skill Learning - Palmer, Jacqueline A.; Halter, Alice; Gray, Whitney; Wolf, Steven L.; Borich, Michael R. (Frontiers in Human Neuroscience, 2019)
Repeated pairing of electrical stimulation of a peripheral nerve with transcranial magnetic stimulation (TMS) over the primary motor cortex (M1) representation for a target muscle can induce neuroplastic adaptations in the human brain related to motor learning. The extent to which the motor state during this form of paired associative stimulation (PAS) influences the degree and mechanisms of neuroplasticity or motor learning is unclear. Here, we investigated the effect of volitional muscle contraction during PAS on 1) measures of general corticomotor excitability and intracortical circuit excitability, and 2) motor performance and learning. We assessed measures of corticomotor excitability using TMS and motor skill performance during a serial reaction time task (SRTT) at baseline and at 0, 30, 60 minutes post-PAS. Participants completed a SRTT retention test one week following the first two PAS sessions. Following the PAS intervention where the hand muscle maintained an active muscle contraction (PASACTIVE), there was lower short interval intracortical inhibition compared to PAS during a resting motor state (PASREST) and a sham PAS condition (PASCONTROL). SRTT performance improved within the session regardless of PAS condition. SRTT retention was greater following both PASACTIVE and PASREST after one week compared to PASCONTROL. These findings suggest that PAS may enhance motor learning retention and that motor state may be used to target different neural mechanisms of intracortical excitation and inhibition during PAS. This observation may be important to consider for the use of therapeutic noninvasive brain stimulation in neurologic patient populations.